2015
DOI: 10.7439/ijbar.v6i2.1535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxicity Effect of Graded Doses of Moringa oleifera Leaf Extract on Blood Indices Using 20 Adult Wistar Rats

Abstract: Epidemiological studies have indicated that Moringa oleifera leaves are a good source of nutrition and exhibit antioxidant activities. Moringa oleifera is being used for many medicinal and nutritional purposes, since it is widely consumed by all for nutritional and varying medicinal purposes; however there is limited scientific data available regarding excessive consumption of this plant. This study is carried out to evaluate the effect of Moringa oleifera leaf extract on some blood indices. 20 adult wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The doses tested in this study did not reach the LD 50 , and there was no observed histopathological damage in different organs. Previous studies have shown no toxicity or adverse effects in body organs for aqueous leaf extract in rats [36, 44]. However, Assare et al , (2012) [45] observed that supra-supplementation with 3000 mg/kg of aqueous leaf extract reduced albumin serum levels and total protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The doses tested in this study did not reach the LD 50 , and there was no observed histopathological damage in different organs. Previous studies have shown no toxicity or adverse effects in body organs for aqueous leaf extract in rats [36, 44]. However, Assare et al , (2012) [45] observed that supra-supplementation with 3000 mg/kg of aqueous leaf extract reduced albumin serum levels and total protein.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that show no risk in using M. oleifera leaves at various doses; however, most of these data have been derived from studies on plant extract. Therefore, the study of leaf powder consumption brings new knowledge about the safety of this plant while providing options for plant preservation without the loss of nutrients, especially since the leaf of this plant can be used as a vegetable in soup preparations, cooked and mixed in with ground peanut cake or packaged in powder pills [21, 3638]. …”
Section: Discussionmentioning
confidence: 99%